Infrastructure and access to digital technologies as determinants of the pedagogical practices teachers from Santa Bárbara, Honduras - Sabillón Jiménez, Cinthia Margarita (2019)
Contemporary societies typically experience constant technological and social changes at a great speed and intensity. However, school environments do not always manage to adequately support and incorporate those changes, which may be reflected in their pedagogical practices. This gap in supporting and incorporating said changes may be due to various factors; however, despite of them, there have been some experiences of pedagogical practices with digital technologies carried out by teachers in Honduras to support those technological and social changes. This article analyzes and discusses the results of a master’s research in education, where pedagogical practices with digital technologies were studied. The discussion is centered in one of its determining factors in order to understand how infrastructure and access to digital technologies condition the development of pedagogical practices by teachers from Santa Bárbara, Honduras. The research was qualitative in nature and used the case study method. Data analysis was made using the textual-discursive method. The results indicated that schools’ infrastructure, together with digital exclusion, make it difficult to implement digital technologies in pedagogical practices.